PENGARUH PEMBERIAN VIRTUAL REALITY TERHADAP SKALA NYERI PASIEN POST APPENDIKTOMI DI RSUD KABUPATEN KARANGANYAR - nanang; Betty; Yeni (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2025)
Appendectomy is a surgical procedure performed to remove the inflamed appendix caused by appendicitis. Post-appendectomy patients often experience significant pain, which can interfere with their recovery process. This study focuses on the administration of Virtual Reality (VR) therapy to reduce the pain scale in post-appendectomy patients. Postoperative pain management is crucial in patient care to expedite recovery and reduce the risk of complications. The objective of this study was to analyze the effect of VR administration on pain scale in post-appendectomy patients at RSUD Karanganyar. A quantitative pre-experimental design with a One Group Pre-test Post-test approach. The sample consisted of 38 patients who met the inclusion criteria, selected using purposive sampling. Data were collected using the Numeric Rating Scale (NRS) to measure pain intensity before and after VR intervention